Distinguishing contributions to diffuse CO2 emissions in volcanic areas from magmatic degassing and thermal decarbonation using soil gas Rn-222-delta C-13 systematics: Application to Santorini volcano, Greece - Parks, M; Caliro, S; Chiodini, G; Pyle, D; Mather, T; Berlo, K; Edmonds, M; Biggs, J; Nomikou, P; Raptakis, C (2013)
Between January 2011 and April 2012, Santorini volcano (Greece) experienced a period of unrest characterised by the onset of detectable seismicity and caldera-wide uplift. This episode of inflation represented the first sizeable intrusion of magma beneath Santorini in the past 50 years. We employ a new approach using Rn-δ C systematics to identify and quantify the source of diffuse degassing at Santorini during the period of renewed activity. Soil CO flux measurements were made across a network of sites on Nea Kameni between September 2010 and January 2012. Gas samples were collected in April and September 2011 for isotopic analysis of CO (δ C), and radon detectors were deployed during September 2011 to measure (Rn). Our results reveal a change in the pattern of degassing from the summit of the volcano (Nea Kameni) and suggest an increase in diffuse CO emissions between September 2010 and January 2012. High-CO-flux soil gas samples have δ C ∼ 0 ‰. Using this value and other evidence from the literature we conclude that these CO emissions from Santorini were a mixture between CO sourced from magma, and CO released by the thermal or metamorphic breakdown of crustal limestone. We suggest that this mixing of magmatic and crustal carbonate sources may account more broadly for the typical range of δ C values of CO (from ∼ - 4 ‰ to ∼ + 1 ‰) in diffuse volcanic and fumarole gas emissions around the Mediterranean, without the need to invoke unusual mantle source compositions. At Santorini a mixing model involving magmatic CO (with δ C of - 3 ± 2 ‰ and elevated (Rn)/CO ratios ∼ 10 - 10 Bq kg) and CO released from decarbonation of crustal limestone (with (Rn)/CO ∼ 30-300 Bq kg, and δ C of + 5 ‰) can account for the δ C and (Rn)/CO characteristics of the 'high flux' gas source. This model suggests ∼ 60 % of the carbon in the high flux deep CO end member is of magmatic origin. This combination of δ C and (Rn) measurements has potential to quantify magmatic and crustal contributions to the diffuse outgassing of CO in volcanic areas, especially those where breakdown of crustal limestone is likely to contribute significantly to the CO flux. © 2013 Elsevier B.V. All rights reserved.